Enhancing Self-Efficacy Through Gamified Learning: Evidence from Arabic Morphology (Ṣarf) Instruction in Higher Education - Abdul Ghofur; Ariga Bahrodin; Siti Durotun Naseha; Immas Anggung Mestuti Kaprawiran; Rizki Fitra Rahman; Ittaqi Haitsumakunti; Abdullah Syamil Imanuddin; Roudhotul Jannah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Arabic morphology (Ṣarf) is widely regarded as one of the most challenging components of Arabic language learning, often resulting in low learner confidence and limited engagement. Despite the growing adoption of gamification in language education, empirical evidence regarding its influence on learners’ self-efficacy in Arabic morphology remains scarce. This study examines the effectiveness of gamified learning in enhancing students’ self-efficacy in Ṣarf instruction. A quasi-experimental pretest–posttest control group design was employed involving 50 undergraduate students enrolled in an Arabic Language Education program. Participants were assigned to experimental and control groups. Data were collected using a validated self-efficacy questionnaire and supported by qualitative reflections. Instrument validity was established through expert review, while reliability was confirmed using Cronbach’s Alpha. Quantitative data were analyzed using paired-samples and independent-samples t-tests, complemented by qualitative thematic analysis. The findings revealed a statistically significant difference between the experimental and control groups, with students exposed to gamified learning demonstrating higher levels of self-efficacy (p = 0.026). Qualitative evidence further indicated that gamified activities promoted engagement, challenge, and sustained learning motivation, which strengthened learners’ confidence in mastering morphological concepts. These findings suggest that gamified learning represents an effective pedagogical approach for fostering self-efficacy in Arabic language education. The study contributes to the emerging literature on gamification by providing empirical evidence from Arabic morphology instruction, a context that remains underrepresented in current research.